Vertical transmission in chikungunya infection - Senanayake, M. P.; Senanayake, S. M.; K K Vidanage, K. K.; S Gunasena, S.; S P Lamabadusuriya, S. P. (Sri Lanka Medical Association, 2009)
We report the pregnancy outcome and clinical and laboratory findings in infants born to women with chikungunya infection during pregnancy. There was evidence of vertical transmission and poor pregnancy outcome in some cases.
Keywords: chikungunya; vertical transmission